2022
DOI: 10.3390/plants11172276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Commercial Arbuscular Mycorrhizal Inoculants on Plant Productivity and Intra-Radical Colonization in Native Grassland: Unintentional De-Coupling of a Symbiosis?

Abstract: There has been a surge in industries built on the production of arbuscular mycorrhizal (AM) fungal-based inoculants in the past few decades. This is not surprising, given the positive effects of AM fungi on plant growth and nutritional status. However, there is growing concern regarding the quality and efficacy of commercial inoculants. To assess the potential benefits and negative consequences of commercial AM fungal inoculants in grasslands, we conducted a controlled growth chamber study assessing the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Commercial inocula very often fail to establish in field conditions, often due to competitive effects with local indigenous species [ 62 ]. Indeed, commercial inocula have been found to benefit invasive species, while reducing growth of native plants from American grasslands [ 63 ]. A detailed analysis of the fate of AM species in the inoculum and the effects on the composition of indigenous communities is clearly needed, yet such analyses are very rarely carried out in mycorrhizal studies [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial inocula very often fail to establish in field conditions, often due to competitive effects with local indigenous species [ 62 ]. Indeed, commercial inocula have been found to benefit invasive species, while reducing growth of native plants from American grasslands [ 63 ]. A detailed analysis of the fate of AM species in the inoculum and the effects on the composition of indigenous communities is clearly needed, yet such analyses are very rarely carried out in mycorrhizal studies [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing demand for biofertilizers, results from commercial AMF inoculants have been largely context-dependent, especially under field conditions, contrary to the common laboratory successes [ 29 , 30 , 31 , 32 ]. The inconsistent narrations from the research community regarding the reliability of AMF inoculation as a valid agricultural management technique [ 33 ] are generating low consumer confidence that is hindering large-scale adoption of the technology.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most microbial inoculants are selected based on their expressed functional traits in a greenhouse, without proper consideration of the ecologically relevant traits that determine establishment and persistence under natural conditions [ 36 ]. While many cases of inoculation failures could be attributed to poor product quality stemming from the lack of regulatory or quality control frameworks that mandate best practices, resulting in a market flooded by substandard products [ 29 , 32 , 37 ], there is also lack of understanding of ecology and of the mode of action of inoculants [ 38 ]. Duell et al [ 29 ] recently demonstrated that inoculants could decouple native plant symbiosis with indigenous strains in a natural ecosystem already containing a large diversity of AMF community, without conferring additional benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symbioses with AMF are especially crucial for the uptake of slow-moving soil nutrients [1]. In nature, DSE and AMF colonize plant roots at the same time, which is frequent in plant ecosystems [14]. Despite the presence of DSE and AMF in plant roots, there has been little research into these symbioses as a whole, and existing information regarding DSE and AMF is uneven [15].…”
Section: Introductionmentioning
confidence: 99%